Solid state recycling of pure Mg and AZ31 Mg machining chips via spark plasma sintering. (5th November 2016) - Paraskevas, Dimos; Dadbakhsh, Sasan; Vleugels, Jef; Vanmeensel, Kim; Dewulf, Wim; Duflou, Joost R.
Abstract: This work investigates the applicability of spark plasma sintering (SPS) as a solid state recycling technique for magnesium alloy scrap. In this respect, machining chips from pure Mg and AZ31 Mg alloy ingots are chemically cleaned, cold compacted and SPSed directly into bulk specimens. It is found that SPS can successfully establish full densification and effective metallurgical bonding between chips without altering compositional constituents. This is attributed to the dynamic compaction during sintering as well as to the disruption of the chips' surface oxide film due to SPS electric current based joule heating. Apart from the successful consolidation, microstructural analysis of the initial Mg ingots, chips and SPS recycled material reveals that the SPS microstructure was finer than that of the original ingots due to significant deformation induced grain refinement during machining. As a result, the recycled materials had a higher compression and shear strength than that of the starting ingot material. The findings indicate that SPS is an effective alternative method for solid state recycling of magnesium alloy scrap. Graphical abstract: Highlights: Spark plasma sintering is found to be a successful solid state recycling technique for the consolidation of Mg alloy chips. Fast and full densification/consolidation of Mg alloy machining chips directly into bulk semi-finished products was acheived. The total recycling route resulted in a finer microstructure than that of the parent material. The strong bonding and the finer microstructure of the recycled samples improved the mechanical properties.